2011
DOI: 10.1111/j.1472-4669.2011.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Legacies of recent environmental change in the benthic communities of Lake Joyce, a perennially ice-covered Antarctic lake

Abstract: Many Antarctic lakes provide habitat for extensive microbial mats that respond on various timescales to environmental change. Lake Joyce contains calcifying microbialites and provides a natural laboratory to constrain how environmental changes influence microbialite development. In Lake Joyce, depth-specific distributions of calcitic microbialites, organic carbon, photosynthetic pigments and photosynthetic potential cannot be explained by current growth conditions, but are a legacy of a 7-m lake level rise bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(78 citation statements)
references
References 50 publications
(114 reference statements)
2
76
0
Order By: Relevance
“…() assembled data to show interannual variation in the transmission of the ice cover of Lake Hoare, one of the MDV lakes, from 0.1 to 2.5% of surface incident. More recently, an order of magnitude spatial variability of light penetration has been documented in Lake Joyce (Hawes et al ., ) and the west lobe of Lake Bonney (Obryk, Doran & Priscu, ), and these authors note that this heterogeneity propagates to depths of at least 10 m. Such variability, in a severely light‐limited environment (Priscu et al ., ; Moorhead, Schmeling & Hawes, ; Hawes et al ., ), can be expected to lead to substantial changes in community photosynthesis and potential for growth over time. For example, Doran et al .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…() assembled data to show interannual variation in the transmission of the ice cover of Lake Hoare, one of the MDV lakes, from 0.1 to 2.5% of surface incident. More recently, an order of magnitude spatial variability of light penetration has been documented in Lake Joyce (Hawes et al ., ) and the west lobe of Lake Bonney (Obryk, Doran & Priscu, ), and these authors note that this heterogeneity propagates to depths of at least 10 m. Such variability, in a severely light‐limited environment (Priscu et al ., ; Moorhead, Schmeling & Hawes, ; Hawes et al ., ), can be expected to lead to substantial changes in community photosynthesis and potential for growth over time. For example, Doran et al .…”
Section: Introductionmentioning
confidence: 91%
“…While the best known of the primary production pathways in the MDV lakes is the phytoplankton (Priscu et al ., ; Laybourn‐Parry & Pearce, ), these have a limited ability to record change. In contrast, the microbial mats are less well known, but are conspicuous contributors to diversity and productivity in the euphotic zones of these lakes, are perennial and contain laminations that record annual net accumulation (Hawes & Schwarz, ; Hawes et al ., ; ; ; Quesada et al ., ). Furthermore, there is evidence that irradiance directly limits the rate of photosynthesis in the mat communities (Vopel & Hawes, ; Hawes, Giles & Doran, ), and hence their potential for growth.…”
Section: Introductionmentioning
confidence: 99%
“…In Lake Joyce, the lake level has risen 7 m between 1973 and 2009 due to increased meltwater influx, at least partly due to an increase in solar radiation and a gradual summer warming trend in the McMurdo Dry Valleys (Bomblies et al ., ). New microbial mats are forming at the margins of Lake Joyce at a rate of millimeters per year, while established mats and microbialites, which formed in shallow water but are now located below 13–16 m, are no longer receiving sufficient irradiance for growth (Hawes et al ., ). Thus, the larger microbial structures in deep water of this lake now represent legacies of previously favorable environmental conditions for phototrophic growth.…”
Section: Antarctic Lakesmentioning
confidence: 97%
“…Less commonly reported are Deinococcus‐Thermus , Planctomycetes , Verrucomicrobiales , and others (Brambilla et al ., ; Antibus et al ., ; Peeters et al ., ; Varin et al ., ). Diatoms may be absent (Anderson et al ., ), present at low levels alongside dominant Cyanobacteria (Sutherland, ; Hawes et al ., ), or in some cases present as the dominant phototrophs (Fernández‐Valiente et al ., ). Other Eucarya such as green algae, fungi, and tardigrades have been noted in a wide range of mats (Verleyen et al ., ).…”
Section: Antarctic Lakesmentioning
confidence: 99%
“…Instead, absorption at 755 nm was recorded, and Bchl a was estimated using the absorption coefficient given by Scheer (44). HPLC analysis was carried out as described by Hawes et al (45), and Bchl c, Bchl d, and Bchl e were identified using diode array spectra (400 to 800 nm) and extinction maxima assembled by Scheer (44). The absorption of each of these pigments at 665 nm was recorded, and the percent contributions of Chl a, Bchl c, Bchl d, and Bchl e to the measured 665-nm absorption were calculated, assuming absorption to be additive.…”
Section: Methodsmentioning
confidence: 99%